PSYCHOLOGICAL TRANSFORMATION OF PERSONALITY IN THE ERA OF GLOBAL CHANGE AND FAIRY -TALE’S ALLEGORICAL SPACE - Muradyan , Ye.B. (Modern Psychology, 2019)
The article considers the process of globalization from the point of view of its influence on a person. Are emphasized some changes in “categorical system of psychology”, taking into consideration substantial transformation of psychological categories, which is also explained by the influence of globalization on a person. Global change era’s characteristic features in the wide range are as well considered. Particular attention is being focused on “psychological transformation of personality” in connection with the processes of globalization. Fairy-tale’s allegorical space, as mean and method, is attempted to be practiced in order to explain “personality transformations” under the influence of globalization.
Keywords: globalization, psychological transformation of personality, metaphore, fairy tale’s allegorical space